(untitled) (Orkopata. Revista de Lingüística, Literatura y Arte, 2023)
In Mexico, extensive research has been carried out where the issue of learning styles is addressed. In the Faculty of Informatics Mazatlán, in the Computer Science Degree program, of the 2018-2019 school year, a high rate of failed subjects, high rates of school dropout, have been perceived over the years and at the same time today. resulting in the low rate of graduation of professionals in Computer Science. This research investigates student problems such as: the high failure rates of the LI program subjects, the early dropout of the student cohorts and the low graduation rate seen in previous school cycles. The quantitative approach was followed using the Honey-Alonso learning styles questionnaire (CHAEA) to the students of the aforementioned program and the VARK questionnaire by Fleming (2006). It was identified that students use a reflective learning style and teachers use a kinesthetic teaching style that are not compatible with each other. From there, the results conclude that the incompatibility of styles is one of the main problems perceived in the Faculty of Informatics Mazatlán.